An association optimization algorithm for wireless access points based on graph transformation - Wen TAO; Yan SHEN; Xinjie GUAN; Xili WAN (Dianxin kexue)
Wireless access point association problem is one of the fundamental problems for Wi-Fi systems.Existing studies focus on the AP association problems under the bandwidth capacity constrain,without considering bandwidth demand for users.Considering the user bandwidth demands,the access point association problem for a Wi-Fi system under hybrid network architecture was studied,with the objective of maximum bandwidth allocation.Different from existing studies,by utilizing graph transformation techniques,this optimization problem was transformed to a network flow optimization problem on a flow graph.Then,an algorithm was proposed based on the maximum network flow problem.Theoretic proof for the optimality of the algorithm was presented and simulations results further validated the superiority of the proposed algorithm.